Too easy? The influence of task demands conveyed tacitly on prospective memory - Lourenço, Joana S.; Hill, Johnathan H.; Maylor, Elizabeth A. (Frontiers in Human Neuroscience, 2015)
Previous research suggests that when intentions are encoded, participants establish an attention allocation policy based on their metacognitive beliefs about how demanding it will be to fulfill the prospective memory (PM) task. We investigated whether tacit PM demands can influence judgments about the cognitive effort required for success, and, as a result, affect ongoing task interference and PM performance. Participants performed a lexical decision task in which a PM task of responding to animal words was embedded. PM demands were tacitly manipulated by presenting participants with either typical or atypical animal exemplars at both instructions and practice (low vs. high tacit demands, respectively). Crucially, objective PM task demands were the same for all participants as PM targets were always atypical animals. Tacit demands affected participants’ attention allocation policies such that task interference was greater for the high than low demands condition. Also, PM performance was reduced in the low relative to the high demands condition. Participants in the low demands condition who succeeded to the first target showed a subsequent increase in task interference, suggesting adjustment to the higher than expected demands. This study demonstrates that tacit information regarding the PM task can affect ongoing task processing as well as harm PM performance when actual demands are higher than expected. Furthermore, in line with the proposal that attention allocation is a dynamic and flexible process, we found evidence that PM task experience can trigger changes in ongoing task interference.